The wedding plot - Munier, Paula (A Mercy Carr Mystery, 2022)
"The Wedding Plot, USA Today bestselling author Paula Munier's fourth Mercy Carr mystery, finds Mercy and Elvis at a deadly Vermont wedding. Love never dies a natural death.... When Mercy's grandmother Patience marries her longtime beau Claude Renault at the five-star Lady's Slipper Inn, it promises to be the destination wedding of the year. Just as the four-day extravaganza is due to begin, the inn's spa director Bodhi St. George disappears-and Mercy's mother Grace sends Mercy and Elvis to find him. But what they discover instead is a stranger skewered by a pitchfork in the barn on the goat farm where St. George lived. As Mercy tries to figure out who the victim is and where St. George is hiding, the bride and groom's estranged relations gather for the first of the pre-wedding festivities. Long-buried rivalries and resentments surface-and Mercy realizes that they're all keeping secrets that could tear both families apart. When Elvis interrupts the escalating melodrama to alert Mercy to an intruder on the estate, she finds a wounded St. George in the cottage where she and Troy are staying. St. George is not who he says he is-but when he escapes from the hospital and disappears again, Mercy thinks he's gone for good. With the wedding imminent and the families at each other's throats, she decides finding St. George will have to wait. The big day arrives-and one of the groomsmen shows up dead. Now the danger is up-close and personal. With the wedding held hostage, it's up to Mercy and Elvis together with Troy and Susie Bear to stop the killer and save the bride and groom-before death do they part"--